Locally defined measures of successful forest co-management: A case study of Tl'azt'en Nation and the John Prince Research Forest. - Quinn, Sarah E. (Author); Fondahl, Gail (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2008)
In Canada, First Nations rights and title to lands and resources have been recognized however, reconciliation of land use conflicts has proven difficult. Co-management is emerging as a potential process for sharing authority between First Nations and others, though evaluative tools are required. This thesis builds on research by UNBC and Tl'azt'en Nation on adaptive forest co-management of the John Prince Research Forest. Through a case study, it presents a method for working with local First Nations to develop measures of co-management success. The method engages 'local experts' through a modified Nominal Group Technique, with an iterative, participatory approach. Results include a set of locally-defined measures on cultural revitalization, characteristics of effective Tl'azt'en measures, and a method evaluation. The method successfully engaged participants in generating effective measures, and constructive participant feedback was received. Implementation of a monitoring program by the John Prince Research Forest is required prior to complete evaluation. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1362346